LEGAL CONSEQUENCES OF ELECTRONIC AGREEMENTS REVIEWED FROM ARTICLE 1866 OF THE CIVIL CODE - Gusti Putu Krisna Murti AV; Dewa Gede Pradnyana Yustiawan (Transpublika Publisher, 2023)
Legal issues with regard to authenticity, authenticity, and proof arise frequently because no laws exist to control the private information of users of electronic agreements. The aim of this research is to determine whether or not there are issues with the legal binding force of agreements established via electronic means. This study employs a normative qualitative approach, based on the analysis of secondary data and bolstered by original data collected in the field. The findings prove that digital investigative tools can be used to verify the legitimacy, veracity, and integrity of electronic contracts. A person's permission is required before any of their personally identifiable information (PHI) can be used in any way, shape, or form via technological media. The evidentiary weight of an electronic or digitally signed deal is the same as that of a handwritten one. As progress is made toward open proof, the judicial system can make use of the system. Given the prevalence of online media in modern business dealings, it follows that any evidence acquired from any source, provided it is true, is admissible so long as it does not violate public order.